Spectroscopy of biological nanocrystals. Issue 1 (2007) - Ortac Ortac, Inanc Inanc; Severcan Severcan, Feride Feride
Abstract : Nanocrystals have gained much interest in recent years, due to their unusual properties allowing interesting applications in physical and biological science. In this literature review, biological nanocrystals are discussed from the spectroscopic point of view. Firstly, the theory behind the outstanding abilities of the nanocrystals is described. Secondly, the spectroscopic properties of biological nanocrystals are mentioned. Lastly, the use of nanocrystals with various spectroscopic applications is reviewed such as biosensor applications with UV–visible and surface plasmon resonance and Raman spectroscopy of biological materials. Finally, a short discussion of infrared nanocrystals and their abilities are included in the review.